2018
DOI: 10.14710/jitaa.43.2.124-130
|View full text |Cite
|
Sign up to set email alerts
|

Indirect evaluation of digestive tract function on male lambs and ram based on feed digestibility and eating behavior

Abstract: This studywasaimed to examine the development and function ofdigestive organsof lamb in digesting feed based on feed digestibility valueandeating behaviour. The materials used were 11 lambs aged 3-4 months, body weight(BW)14.78 ± 1.99 kg (CV 3.98%), and 11 ramsaged 10-12 months, BW 22.18 ± 1.81 kg (CV 3.29%). The study used a completelyrandomized design of 2x2 in nestedpatterns. There were two ages compared (lambs vs ram) and every age was nested the diet i.e.100%Napiergrass (G100) vs mixed pellet 50% grass an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…This result was attributed to the fact that DMI of the young goat was lower than that of the mature goat, while DM digestibility of the both ages of goat was similar. The result of this study was in agreement with the finding of Prima et al (2018) that different DMI accompanied by similar DM digestibility resulted in different DDMI.…”
Section: Feed Intake and Digestibilitysupporting
confidence: 92%
See 1 more Smart Citation
“…This result was attributed to the fact that DMI of the young goat was lower than that of the mature goat, while DM digestibility of the both ages of goat was similar. The result of this study was in agreement with the finding of Prima et al (2018) that different DMI accompanied by similar DM digestibility resulted in different DDMI.…”
Section: Feed Intake and Digestibilitysupporting
confidence: 92%
“…The similarity of DM digestibility in both ages of goats (Table 2) indicated that the digestive tract of the young had well developed, so that the young was able to digest the feed as well as the mature goat did. The result of this study was in agreement with the finding of Prima et al (2018) that digesting ability of the lamb aged 4 months was similar to that of the ram aged 12 months. Dry matter digestibility of diet G3C7 was significantly higher (P<0.05) than that of diet G7C3 (Table 2), both in the young and the mature goats.…”
Section: Feed Intake and Digestibilitysupporting
confidence: 92%
“…Intake of OM showed the same response to the diets as of DM. The intake of OM is strongly influenced by DM intake (Prima et al, 2018).…”
Section: Feed Intake and Digestibilitymentioning
confidence: 99%